GENETIC VARIATION OF TEAK MISTLETOE (Dendrophthoe pentandra (L.) Miq.) BASED ON RANDOM AMPLIFIED POLYMORPHIC DNA (RAPD) MARKERS - Zainal Muttaqin; Sri Wilarso Budi; Basuki Wasis; Iskandar Zulkarnaen Siregar; Corryanti Corryanti (SEAMEO BIOTROP, 2020)
Mistletoes are hemiparasitic macroparasite plants that interfere with trees and other wild plants in nutrient acquisition. As the plant has low leaf water potential, it draws water from teak wood tissues during the deciduous stage of the teak host, thereby killing the twigs and eventually the teak tree. Mistletoes are also key players in plant diversity. Therefore, the mistletoe population needs to be regulated not only as a parasite but also as a keystone species affecting biodiversity. Knowledge scarcity on the status of mistletoes includes their genetic variation. Hence, the purpose of this study is to analyze the level of genetic variation of teak mistletoe (Dendrophthoe pentandra) using RAPD markers. At the Padangan teak Clonal Seed Orchard (CSO), leaf samples were randomly collected from three layers of the mistletoe crown (upper, middle, and below) taken from five host teak trees randomly selected from each of the sub-observation measure plots (OMP). Four OMP units inside the observation sample plots (OSP) (n = 3, 50 × 50 m) at different levels of infestation (light, moderate, and heavy) were established. Analysis of genetic variation and genetic distance of mistletoes across different crown layers was conducted using RAPD markers. The leaf samples from crown layers UU (upper crown, subsection upper), UM (upper crown, subsection middle), and UB (upper crown, subsection below), including U (upper crown), had significantly greater genetic variation (He = 0.181–0.255) than those from the M layer (middle crown, He = 0.227) and the B layer (below crown, He = 0.114). Furthermore, the greatest genetic distance occurred between mistletoes in the UB and B crown layers (0.310), whereas the shortest genetic distance occurred between mistletoes of the UU and UM layers in the upper crown (0.038). Practical implications of the low genetic variation include the control of D. pentandra infestation by restricting its population so that the Perhutani State-Owned Forestry Enterprise can maintain damage levels below the economic threshold.